New Japanese narratives and the disarticulation of male hegemony: Discursive diversification through the hybridization of genres in contemporary manga - Martínez Alcaide, Fabio; Venet-Gutiérrez, Jacqueline (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Manga has established itself as one of the world's most profitable publishing industries, becoming a major artistic movement of the 21st century whose influence has permeated other media such as film, music, video games and fashion. This article attempts to identify the existence of a general semantics in manga narrative, as well as its industrial influence. This leads us to predict the disappearance of its commercial genres due to a process of hybridization that is occurring in contemporary productions, implying the dismantling of the male hegemony rooted in it for decades.